The art of people management in libraries : Tips for managing your most vital resource - McKinlay, James, MHRD (Chandos information professional series., 2010)
This book explores recent trends in human resource management practices and presents options for their application within the special context of libraries, especially academic and research libraries. It lays out a set of the most pressing HR management issues facing senior library leaders in the context of continuous organisational change in the 21st century and offers library practitioners effective tips for people management.